DIFFERENT ACUTE METABOLISM OF FRUCTOSE IN DIALYSIS PATIENTS COMPARED TO HEALTHY SUBJECTS - Björn Anderstam; Ann-Christin Br; Jonas Axelsson; Abdul Rashid Qureshi; Rolf Wibom; Bengt Lindholm; Peter Stenvinkel (The Korean Society of Nephrology, 2012)
The consumption of fructose has increased dramatically during the last two decades and parallels the epidemics of obesity, metabolic syndrome, diabetes and chronic kidney disease ADDIN EN.CITE ADDIN EN.CITE.DATA . Fructose comes naturally e.g. in fruit and in honey, both sole as monosaccharide and as sucrose. High-fructose corn syrup is an American substitute for sucrose containing 55% fructose. 6 HD-patients and 9 healthy subjects consumed 190 ml cream and 75 g sucrose. Fructose and uric acid were analyzed postprandially during 240 min. For this study we used a new sensitive fructose assay. Fat/carbohydrate loading resulted in different acute fructose responses (see figure) and whereas uric acid levels remained stable in controls, it increased by 10 % in HD patients.fx1 We conclude that a fatty meal is associated with a delayed post-prandial fructose absorption and/or metabolism, as well as increased uric acid levels in HD patients. In an ongoing new study, the fructose metabolism will be further studied in CKD patients, diabetics and healthy controls.